Viruses in the desert: a metagenomic survey of viral communities in four perennial ponds of the Mauritanian Sahara - Fancello, Laura (Nature Publishing Group, 2013)
Here, we present the first metagenomic study of viral communities from four perennial ponds (gueltas) located in the central Sahara (Mauritania). Three of the four gueltas (Ilij, Molomhar and Hamdoun) are located at the source of three different wadis belonging to the same hydrologic basin, whereas the fourth (El Berbera) belongs to a different basin. Overall, sequences belonging to tailed bacteriophages were the most abundant in all four metagenomes although electron microscopy and sequencing confirmed the presence of other viral groups, such as large DNA viruses. We observed a decrease in the local viral biodiversity in El Berbera, a guelta with sustained human activities, compared with the pristine Ilij and Molomhar, and sequences related to viruses infecting crop pests were also detected as a probable consequence of the agricultural use of the soil. However, the structure of the El Berbera viral community shared the common global characteristics of the pristine gueltas, that is, it was dominated by Myoviridae and, more particularly, by virulent phages infecting photosynthetic cyanobacteria, such as Prochlorococcus and Synechococcus spp. In contrast, the Hamdoun viral community was characterized by a larger proportion of phages with the potential for a temperate lifestyle and by dominant species related to phages infecting heterotrophic bacteria commonly found in terrestrial environments. We hypothesized that the differences observed in the structural and functional composition of the Hamdoun viral community resulted from the critically low water level experienced by the guelta.